2021
DOI: 10.1111/opo.12797
|View full text |Cite
|
Sign up to set email alerts
|

An implementation of Bubble Magnification did not improve the video comprehension of individuals with central vision loss

Abstract: Purpose: People with central vision loss (CVL) watch television, videos and movies, but often report difficulty and have reduced video comprehension. An approach to assist viewing videos is electronic magnification of the video itself, such as Bubble Magnification. Methods: We created a Bubble Magnification technique that displayed a magnified segment around the centre of interest (COI) as determined by the gaze of participants with normal vision. The 15 participants with CVL viewed video clips shown with 2× a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In a separate multicenter prospective trial with 51 participants using a separate head-mounted display device, similar functional improvements were observed in overall visual ability, reading, and visual information tasks. 5 However, Costela et al 19 found a deterioration in performance for video comprehension using a similar virtual bioptic display for people with good vision.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate multicenter prospective trial with 51 participants using a separate head-mounted display device, similar functional improvements were observed in overall visual ability, reading, and visual information tasks. 5 However, Costela et al 19 found a deterioration in performance for video comprehension using a similar virtual bioptic display for people with good vision.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas VR allows for people with low vision to experience otherwise unsafe tasks in a controlled virtual environment, AR is better suited as a real-life visual accessibility aid ( Gopalakrishnan, Chouhan Suwalal, Bhaskaran, & Raman, 2020 ), as it is allows for real-time interaction with an overlay of the real and digital world (similar to a hearing aid). Augmentation studies in this category focused on a variety of tasks, ranging from reading to face recognition (e.g., Costela, Reeves, & Woods, 2021b , 2021a ; Calabrèse et al., 2018 ) and obstacle avoidance (e.g., Huang et al., 2019 ; Angelopoulos, Ameri, Mitra, & Humayun, 2019 ). Similar to the previous section, most of the studies in this category evaluated their augmentation prototype either directly on people with low vision (e.g., Calabrèse et al., 2018 ; Houston, Bowers, Peli, & Woods, 2018 ) or indirectly by using low-vision simulations with sighted participants (e.g., Hwang & Peli, 2014 ; van Rheede et al., 2015 ; Foster, Hotchkiss, Buckley, & Elliott, 2014 ).…”
Section: Research Areasmentioning
confidence: 99%